2018
DOI: 10.1371/journal.pone.0203171
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the exposure to cumulative cardiovascular health behaviors and factors and chronic kidney disease—The Kailuan study

Abstract: It is unclear whether ideal cardiovascular health (CVH) behaviors and factors, particularly cumulative exposure to ideal CVH (cumCVH), is associated with chronic kidney disease (CKD). The aim of the study was to examine the effect of cumCVH on CKD using the data from the Kailuan study. The study included the 27,970 (21,199 males) of the Kailuan community (China). The participants were 19 to 98 years of age. They were followed in 2008–2009, 2010–2011, and 2012–2013 by the same medical staff that did the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 28 publications
(34 reference statements)
1
13
0
Order By: Relevance
“…Individual-level data analysis conducted on 34 multinational cohorts from the CKD Prognosis Consortium, including 5 222 711 subjects from 28 countries, indicated that among diabetic and non-diabetic individuals, hypertension, having higher BMI, and ever smoker were significant predictors of CKD development [ 32 ]. Similar to our study, previous studies have also found that being in the healthier categories of BMI, BP and FPG was associated with a lower risk of CKD [ 11 , 19 , 20 ]. The results derived from the ARIC study showed that being in the intermediate and ideal categories of BMI was associated with 20% and 26% reduced risk of CKD, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Individual-level data analysis conducted on 34 multinational cohorts from the CKD Prognosis Consortium, including 5 222 711 subjects from 28 countries, indicated that among diabetic and non-diabetic individuals, hypertension, having higher BMI, and ever smoker were significant predictors of CKD development [ 32 ]. Similar to our study, previous studies have also found that being in the healthier categories of BMI, BP and FPG was associated with a lower risk of CKD [ 11 , 19 , 20 ]. The results derived from the ARIC study showed that being in the intermediate and ideal categories of BMI was associated with 20% and 26% reduced risk of CKD, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Another study assessed the association of ICVHM and ESRD; it showed a graded association between a higher score of ICVHM and a lower incidence rate of ESRD, as those with 4 ICVHM had about 50% lower risk for the event compared to the reference category. However, this association was no longer significant after adjusting for eGFR, while our significant HRs persisted [ 11 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations